2014
DOI: 10.1542/peds.2013-1844
|View full text |Cite
|
Sign up to set email alerts
|

Decreasing Handoff-Related Care Failures in Children’s Hospitals

Abstract: BACKGROUND AND OBJECTIVE: Patient handoffs in health care require transfer of information, responsibility, and authority between providers. Suboptimal patient handoffs pose a serious safety risk. Studies demonstrating the impact of improved patient handoffs on care failures are lacking. The primary objective of this study was to evaluate the effect of a multihospital collaborative designed to decrease handoff-related care failures.METHODS: Twenty-three children' s hospitals participated in a quality improvemen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
62
0
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 89 publications
(70 citation statements)
references
References 16 publications
3
62
0
2
Order By: Relevance
“…6,9,18,19 However, these studies did not specifically measure the potential benefit on the efficiency of care delivery often associated with standardization in high-reliability systems. 20 A small number of studies have measured handover time as a balancing metric; these 5 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…6,9,18,19 However, these studies did not specifically measure the potential benefit on the efficiency of care delivery often associated with standardization in high-reliability systems. 20 A small number of studies have measured handover time as a balancing metric; these 5 …”
Section: Discussionmentioning
confidence: 99%
“…5 Most notably, the implementation of the I-PASS (illness severity, patient summary, action list, situation awareness and contingency plans, and synthesis by receiver)-supported handoff bundle studied with resident-to-resident handoffs has shown reductions in medical errors and preventable adverse events. 1,[6][7][8] Although previous reports have shown important benefits in standardizing handoffs, there is little information available reflecting the association of standardized handoff process with efficiency and culture of safety. One recent report found that a standardized communication process was not associated with an increase in time for handoff between the operating room and the recovery room.…”
mentioning
confidence: 99%
“…The panel evaluated the existing literature and adopted tools and change concepts from previous discharge programs. 2, 3, 8 -11, 30 They also incorporated lessons learned e2 20 This panel developed a change package covering 6 broad areas, which included the following strategies:…”
Section: Interventionmentioning
confidence: 99%
“…Child health professionals care about the clinical outcomes of the children they look after. A culture of safety should ensure that they should have robust, timely data that can act as a feedback loop on their performance [21].…”
Section: Introductionmentioning
confidence: 99%
“…The handover is critical, as it requires transfer of clinical information and responsibility between teams. A recent study in 23 US hospitals [21] showed that a standardized handover process could significantly reduce handover failures from a baseline of 25 % to just fewer than 8 %. Ideally, the handover process or bundle needs to be embedded within the electronic medical record.…”
Section: Introductionmentioning
confidence: 99%